2008
DOI: 10.1103/physrevb.77.045134
|View full text |Cite
|
Sign up to set email alerts
|

One-dimensional structured ultrasonic metamaterials with simultaneously negative dynamic density and modulus

Abstract: We present theoretically a type of one-dimensional ͑1D͒ structured ultrasonic metamaterial that exhibits a forbidden band where both the effective dynamic density and bulk modulus are simultaneously negative. The material consists of a 1D array of repeated unit cells with shunted Helmholtz resonators. The transmission coefficient, wave vector, negative dynamic density, and modulus are determined by means of the acoustic transmission line method ͑ATLM͒. The double negativity in the effective dynamic density and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
108
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(113 citation statements)
references
References 24 publications
1
108
0
3
Order By: Relevance
“…It was subsequently suggested that acoustic/elastic LHMs could be constructed by mixing two structures that independently exhibit negative density and modulus [30]. Negative modulus could be achieved through a periodic array of Helmholtz resonators [31,32], and the negative density could be achieved through an array of thin membranes [33]. The combination of these two structures was shown to exhibit LHM properties [34,35] Since then, researchers have proposed more complicated acoustic/elastic LHM architectures.…”
Section: Emergence Of Negative and Tensorial Materials Propertiesmentioning
confidence: 99%
“…It was subsequently suggested that acoustic/elastic LHMs could be constructed by mixing two structures that independently exhibit negative density and modulus [30]. Negative modulus could be achieved through a periodic array of Helmholtz resonators [31,32], and the negative density could be achieved through an array of thin membranes [33]. The combination of these two structures was shown to exhibit LHM properties [34,35] Since then, researchers have proposed more complicated acoustic/elastic LHM architectures.…”
Section: Emergence Of Negative and Tensorial Materials Propertiesmentioning
confidence: 99%
“…The general form of the effective bulk modulus, B e f f , of acoustic waves is given by the complex form similar to the effective electric permittivity in electric metamaterials 12,14,15,17,18 …”
Section: Theorymentioning
confidence: 99%
“…Metamaterials are phononic crystals that can be micro-architecturally designed for high stress-wave attenuation (Liu et al, 2000;Ho et al, 2003;Cheng et al, 2008;Huang and Sun, 2009). They have overall mechanical properties that are not shared by traditional engineering materials (Guenneau et al, 2007;Torrent and Sanchez-Dehesa, 2007;Milton and Willis, 2007;Torrent and Sanchez-Dehesa, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Their results show significant drop in transmission coefficient at resonance frequencies and they used it to make a broadband sonic shield. Cheng et al (2008) designed a 1-D ultrasonic metamaterial with both effective density and effective bulk modulus simultaneously negative. They found the transmission coefficient using acoustic transmission line method (ATLM), finite element method, and experimental measurement and observed a substantial drop in transmission spectrum around the resonance frequency.…”
Section: Introductionmentioning
confidence: 99%